The Gift of Education: How Indigenous Knowledges Can Transform the Future of Public Education - Jacob, Michelle M.; Sabzalian, Leilani; Jansen, Joana; Tobin, Tary J.; Vincent, Claudia G.; LaChance, Kelly M. (International Journal of Multicultural Education, 2018)
This article advocates for the necessity of Indigenous Knowledges in furthering Indigenous self-determination in public schools, as well as furthering the broad aims of public education. Drawing attention to past efforts across the United States to transform the public school curriculum and analyzing data from testimonies given at Oregon State Legislature Hearings, we argue that Indigenous Knowledges offer an important resource for educating all students responsibly and improving relationships within and across communities. Framing these ideas as gift-giving logic, we argue that if educators and policy-makers are open, they can learn a great deal from Indigenous Knowledges and advocacy efforts.